2024
DOI: 10.1038/s41598-024-56377-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of klotho and fibroblast growth factor 23 in arterial calcification, thickness, and stiffness: a meta-analysis of observational studies

Citrawati Dyah Kencono Wungu,
Hendri Susilo,
Mochamad Yusuf Alsagaff
et al.

Abstract: This meta-analysis was conducted to clarify the role of klotho and fibroblast growth factor 23 (FGF-23) in human arterial remodeling across recent studies, in terms of arterial calcification, thickness, and stiffness. A systematic literature search was conducted on five databases for articles up to December 2023. Arterial calcification, thickness, and stiffness were determined using the calcification score and artery affected, carotid intima–media thickness (CIMT), and pulse wave velocity (PWV), respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Moreover, FGF23, a hormone known for its roles in phosphate and vitamin D metabolism, has been implicated in the pathogenesis of cardiovascular calcifications, particularly through its association with vascular calcification. Wungu et al indicated that FGF23 was associated with arterial calcification, thickness, and stiffness, clarifying their role in arterial remodeling processes [ 38 ]. Our findings do not establish a direct causal relationship between FGF23 levels and cardiovascular calcifications in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FGF23, a hormone known for its roles in phosphate and vitamin D metabolism, has been implicated in the pathogenesis of cardiovascular calcifications, particularly through its association with vascular calcification. Wungu et al indicated that FGF23 was associated with arterial calcification, thickness, and stiffness, clarifying their role in arterial remodeling processes [ 38 ]. Our findings do not establish a direct causal relationship between FGF23 levels and cardiovascular calcifications in the general population.…”
Section: Discussionmentioning
confidence: 99%